PELATIHAN EXCELENSI KEUANGAN SMK MENGASAH KETERAMPILAN LAPORAN KEUANGAN DENGAN SPREADSHEET - Amir Hamzah; Dendi Purnama (LPPM Universitas Bina Bangsa, 2024)
This community engagement initiative aimed to enhance the competence of Vocational School (SMK) students in preparing financial reports using spreadsheets. In this endeavor, we collaborated with an SMK in Kuningan Regency to organize training and practical sessions. The evaluation results demonstrated a significant improvement in students' understanding of financial reports.Before the training, the average exam score of students was 65, with only 75% of students passing the basic financial report knowledge exam. Following the training, the average exam score increased to 85, and the pass rate surged to 95%. These outcomes reflect the success of the training in improving students' comprehension and equipping them with practical skills necessary in the workforce.The significance of these results lies in the enhanced competence of SMK students in preparing financial reports, a skill highly sought after in today's business world. The success of this training attests to the tangible benefits of collaboration between educational institutions and the community in enhancing the quality of education and preparing students for their careers